Pre-lithiation method of lithium ion battery electrode plate
Through the self-discharge reaction between the porous membrane and the electrode sheet of the lithium-ion battery, the problem of the rapid prelithiation reaction rate of the lithium-ion battery is solved, and the uniform prelithiation of the electrode and the improvement of the battery performance are achieved.
Patent Information
- Application Number
- CN202411659112.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing pre-lithiation methods of lithium-ion batteries, the lithiation reaction rate is too fast, resulting in uneven reactions at the electrode interface, affecting the cycle stability and safety of the battery.
The porous membrane is used to contact the electrode sheet of the lithium-ion battery, and prelithiation is carried out through self-discharge reaction. The mechanical strength and reactive activity of the porous membrane are used to achieve uniform lithium ion transmission and electron transmission, and avoid direct contact between lithium metal and electrode material. , regulate the reaction rate.
The uniform prelithiation of lithium-ion battery electrodes is achieved, which improves the energy density and cycle life of the battery, reduces the damage to electrode materials, simplifies the process flow and reduces production costs.
Smart Images

Figure CN119230756A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a pre-lithiation method for a lithium ion battery electrode plate. Background Art
[0002] Lithium-ion batteries have been widely used in many fields such as electric transportation and digital products due to their many advantages such as high energy density and long cycle life. However, during the first charging process of lithium-ion batteries, the side reaction between the negative electrode material and the electrolyte will lead to the loss of active lithium, which not only reduces the initial capacity of the battery, but also may affect the cycle stability and safety of the battery. Pre-lithiation technology is one of the effective ways to solve this problem. It compensates for the lithium consumed by the solid electrolyte interface (SEI) formed during the first charging process by adding additional lithium sources to the electrode material in advance during the battery manufacturing process. This can not only increase the initial capacity of the battery, but also improve the cycle performance of the battery. In order to further improve the performance of lithium-ion batteries, extend their service life, and increase energy density, the research and application of pre-lithiation technology is still developing. At present, many pre-lithiation methods have been invented. Chemical pre-lithiation mainly replenishes lithium through a reducing lithium-containing solution, but the existence of residual problems will have a negative impact on the electrochemical properties of the electrode material. The electrochemical pre-lithiation operation is complicated and requires assembly and disassembly of the battery, which is difficult to achieve practical application. In addition, self-discharge pre-lithiation is a simple method that allows lithium metal to contact an electrode and spontaneously undergo a lithium insertion reaction. The self-discharge pre-lithiation method currently under study has the problem of uneven electrode interface reaction due to the excessively fast lithiation reaction rate, and direct contact between the electrode material and lithium metal will cause damage to the electrode material. Summary of the invention
[0003] The purpose of the present invention is to provide a pre-lithiation method for lithium-ion battery electrode plates to solve technical problems such as excessively fast reaction rates in existing pre-lithiation methods causing uneven electrode interface reactions.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for pre-lithiation of a lithium-ion battery electrode plate, comprising the following steps:
[0006] The lithium-ion battery electrode sheet and the pre-lithiation membrane are stacked in the electrolyte in a roll-to-roll manner, and pre-lithiation is performed after compression, and a spontaneous self-discharge reaction is performed using the potential difference between the pre-lithiation membrane and the lithium-ion battery electrode sheet;
[0007] The pre-lithiation membrane is composed of a porous membrane and a lithium belt;
[0008] The lithium ion battery electrode plate is in direct contact with one side of the porous membrane.
[0009] Furthermore, the porous membrane comprises one of a porous copper foil, a porous nickel foil, a porous titanium foil, a porous stainless steel mesh, a porous copper-zinc-aluminum alloy membrane, a porous carbon membrane and a porous inorganic-organic composite membrane.
[0010] Furthermore, the porous inorganic-organic composite membrane comprises an inorganic component and an organic component, wherein the inorganic component comprises one or more of silver, tin, aluminum, magnesium, indium, lead, gold, platinum, silicon, germanium, bismuth, antimony, lithium titanate and aluminum oxide; and the organic component comprises one or more of cellulose, polyamide, polytetrafluoroethylene, polyester, polypropylene, polyethylene, polyethylene oxide, polyvinyl chloride, polysulfone, polyvinylidene fluoride, polyacrylonitrile and polyether sulfone.
[0011] Furthermore, the pore diameter of the porous membrane is 0.1 to 200 μm, and the thickness of the porous membrane is 10 μm to 5 mm.
[0012] Furthermore, the lithium-ion battery electrode plate is a negative electrode plate or a positive electrode plate.
[0013] Furthermore, the temperature of the self-discharge reaction is 0-50°C.
[0014] Furthermore, the negative electrode plate includes one of a silicon-based negative electrode plate, a graphite negative electrode plate, a silicon-carbon negative electrode plate and a silicon-based negative electrode plate; the positive electrode plate includes one of a lithium cobalt oxide positive electrode plate, a nickel-cobalt-manganese-based ternary positive electrode plate and a sulfur positive electrode plate.
[0015] Beneficial effects of the present invention:
[0016] (1) The pre-lithiation membrane of the present invention has the advantages of good mechanical stability and reusability. A pre-lithiation membrane with high mechanical strength is used to contact pre-lithiate the lithium-ion battery electrode, wherein the lithium metal is the upper layer away from the pole piece, and the porous membrane is the lower layer close to the pole piece. Since a metal membrane or an organic-inorganic composite membrane is composited with a lithium belt, the mechanical strength of the composite pre-lithiation membrane is improved, and the pre-lithiation membrane can be reused.
[0017] (2) The pre-lithiation membrane of the present invention has the advantage of high activity and can achieve uniform pre-lithiation. When the lithium foil and the pole piece are in direct contact for pre-lithiation, chemical corrosion and electrochemical corrosion will occur, resulting in a reduction in the contact sites between the lithium foil and the electrode, causing the activity of lithium to decrease or even become inactivated. The porous membrane can effectively separate the pole piece and the lithium metal, avoid contamination of the lithium metal surface, ensure the activity of the lithium metal material, and can be reused. The porous membrane can achieve stable ion and electron transmission pathways, thereby promoting uniform pre-lithiation.
[0018] (3) The present invention adopts direct contact reaction between metallic lithium and electrode materials, which has the advantages of simple process and suitability for roll-to-roll process. The present invention can achieve precise pre-lithiation of electrode scale, obtain clean, residue-free pre-lithiation of lithium-ion battery electrode sheets, reduce the subsequent cleaning steps, and is suitable for large-scale roll-to-roll pre-lithiation. In addition, before assembling the battery, the pre-lithiation electrode sheet can detect its pre-lithiation degree in real time, which has the advantages of simple operation, low production cost, and easy industrialization.
[0019] (4) The pre-lithiation membrane of the present invention can achieve controllability of pre-lithiation. Conventional contact pre-lithiation is direct contact between lithium and the electrode. Due to the potential difference between lithium metal and the electrode material, ions and electrons are simultaneously transmitted to the surface of the electrode. This reaction is uncontrollable and can easily cause a violent reaction at the contact interface, which in turn leads to unevenness of the electrode. When a pre-lithiation membrane is used, electrons will pass from lithium metal through the porous membrane to the electrode electrode. At the same time, lithium ions will pass from lithium metal through the pores of the porous membrane to the electrode electrode. The combination of electrons and lithium ions achieves the pre-lithiation effect of the electrode electrode. By changing the material and thickness of the porous membrane to adjust the electronic conductivity, and changing the porosity of the porous membrane and the concentration of the electrolyte to regulate the ionic conductivity, the rate of electrode contact pre-lithiation can be regulated, effectively avoiding the problem of too fast lithium ion embedding into the electrode material causing damage to the electrode material, and further improving the uniformity of electrode pre-lithiation.
[0020] (5) The pre-lithiation membrane of the present invention can realize the pre-lithiation (over-lithiation) of the positive electrode. Since the potential difference between lithium and the positive electrode is too large, it is generally impossible to ensure the uniformity and structural stability of lithium when it is directly in contact with the positive electrode for pre-lithiation. The present invention uses the inorganic components of the organic-inorganic composite membrane to react with lithium, such as forming lithium antimony alloy (~1V) or lithiated lithium titanate (~1.5V), which can buffer the potential difference between lithium metal and the electrode, and can thus be used for positive electrode pre-lithiation.
[0021] (6) The method of the present invention uses a porous membrane to separate the electrode and the lithium metal material. Compared with the direct contact in the prior art, the chemical corrosion of the lithium metal material to the electrode can be eliminated, thereby improving the electrochemical stability of the electrode.
[0022] (7) In addition, based on the present invention, by optimizing the parameters such as the elemental metallic lithium material used, the reaction temperature and the contact time, electrode materials with different degrees of lithiation can be obtained.
[0023] In summary, the present invention adopts a pre-lithiation membrane with high mechanical strength and high reactivity, which can realize industrial roll-to-roll pre-lithiation of electrode materials through a simple self-discharge pre-lithiation mechanism. The homogenized pre-lithiation electrode material can compensate for the lithium loss at the negative terminal of the lithium-ion battery, thereby improving the energy density and cycle life of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope (SEM) cross-sectional view of a positive electrode sheet of nickel cobalt manganese oxide that has not been pre-lithiated, has direct contact with the electrolyte, and has a pre-lithiated membrane pre-lithiated;
[0025] Figure 2 This is a SEM top view of a positive electrode sheet of nickel cobalt manganese oxide that has not been pre-lithiated, has direct contact with the electrolyte, and has added membrane pre-lithiation;
[0026] Figure 3 This is the X-ray diffraction (XRD) diagram of the positive electrode sheet of nickel cobalt manganese oxide that has not been pre-lithiated, has direct contact with the electrolyte, and has been pre-lithiated with a pre-lithiated membrane;
[0027] Figure 4 This is the first charge and discharge curve of the pre-lithiated nickel cobalt manganese oxide positive electrode;
[0028] Figure 5 is an optical microscope photograph of the porous membrane in Example 2;
[0029] Figure 6 This is a SEM cross-sectional view of a pre-lithiated silicon negative electrode sheet that has not been pre-lithiated, has direct contact with the electrolyte, and has a porous copper + lithium belt pre-lithiated membrane;
[0030] Figure 7 is the first charge curve of the pre-lithiation silicon negative electrode;
[0031] Figure 8 It is a time-pre-lithiation capacity curve of the pre-lithiation graphite negative electrode;
[0032] Fig. 9 Schematic diagram of the model of the pre-lithiation method of the present invention. DETAILED DESCRIPTION
[0033] The present invention provides a method for pre-lithiation of a lithium-ion battery electrode plate, comprising the following steps:
[0034] The lithium-ion battery electrode sheet and the pre-lithiation membrane are stacked in the electrolyte in a roll-to-roll manner, and pre-lithiation is performed after compression, and a spontaneous self-discharge reaction is performed using the potential difference between the pre-lithiation membrane and the lithium-ion battery electrode sheet;
[0035] The pre-lithiation membrane is composed of a porous membrane and a lithium belt;
[0036] The lithium ion battery electrode plate is in direct contact with one side of the porous membrane.
[0037] The present invention utilizes the potential difference between the pre-lithiation membrane and the electrode plate of the lithium ion battery to carry out a spontaneous self-discharge reaction to achieve a pre-lithiation effect, thereby obtaining a uniformly pre-lithiation electrode plate.
[0038] In the present invention, when the pre-lithiation membrane is in contact with the electrode plate of the lithium-ion battery, the lithium belt is on the side away from the electrode, and the porous membrane is on the side close to the electrode.
[0039] In the present invention, the porous membrane comprises one of porous copper foil, porous nickel foil, porous titanium foil, porous stainless steel mesh, porous copper-zinc-aluminum alloy membrane, porous carbon membrane and porous inorganic-organic composite membrane, preferably one of porous copper foil, porous nickel foil, porous titanium foil and porous inorganic-organic composite membrane.
[0040] In the present invention, the porous inorganic-organic composite membrane comprises an inorganic component and an organic component, and the inorganic component comprises one or more of silver, tin, aluminum, magnesium, indium, lead, gold, platinum, silicon, germanium, bismuth, antimony, lithium titanate and aluminum oxide, preferably one or more of silver, tin, aluminum, magnesium, indium, bismuth, antimony, lithium titanate and aluminum oxide.
[0041] In the present invention, the organic component comprises one or more of cellulose, polyamide, polytetrafluoroethylene, polyester, polypropylene, polyethylene, polyethylene oxide, polyvinyl chloride, polysulfone, polyvinylidene fluoride, polyacrylonitrile and polyether sulfone, preferably one or more of cellulose, polyamide, polytetrafluoroethylene, polyester, polypropylene, polyethylene and polyethylene oxide.
[0042] In the present invention, the pore diameter of the porous membrane is 0.1-200 μm, preferably 10-180 μm, more preferably 50-150 μm, and more preferably 80-100 μm; the thickness of the porous membrane is 10 μm-5 mm, preferably 1 μm-3 mm, and more preferably 0.5 μm-2 mm.
[0043] In the present invention, there is no requirement for the thickness of the lithium ribbon, and the thickness is 10 μm to 1 mm, preferably 50 μm to 500 μm.
[0044] In the present invention, the lithium-ion battery electrode plate is a negative electrode plate or a positive electrode plate.
[0045] In the present invention, the temperature of the self-discharge reaction is 0 to 50°C, preferably 20 to 40°C, and more preferably 25°C.
[0046] In the present invention, the negative electrode plate includes one of a silicon-based negative electrode plate, a graphite negative electrode plate, a silicon-carbon negative electrode plate and a silicon-based negative electrode plate; the positive electrode plate includes one of a lithium cobalt oxide positive electrode plate, a nickel-cobalt-manganese-based ternary positive electrode plate and a sulfur positive electrode plate.
[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] Take 0.9g of lithium nickel cobalt manganese oxide powder, 0.05g of conductive agent (conductive carbon black) and 0.05g of binder (polyvinylidene fluoride), mix the weighed materials evenly, slurry them, apply them, bake them at 80°C under vacuum conditions for 24h, and punch them into electrodes with a diameter of 10mm.
[0050] Lithium titanate nanopowder and polytetrafluoroethylene (PTFE) were prepared into a self-supporting organic-inorganic composite membrane (pore size of 1 μm and thickness of 10 μm) through a dry electrode process. The lithium strip and the composite membrane were assembled together to form a pre-lithiation membrane. In a dry atmosphere, the nickel cobalt manganese oxide positive electrode sheet and the pre-lithiation membrane were closely contacted under the infiltration of electrolyte (1M LiPF6 in EC:EMC:DMC=1:1:1, volume ratio). The NCM electrode sheet of the control group was directly contacted with lithium metal for pre-lithiation, and the reaction reached the same lithiation depth (lithium replenishment capacity reached 40 mAh / g) at 25°C. After drying, the pre-lithiation nickel cobalt manganese oxide positive electrode sheet was obtained. The morphology of the pre-lithiation positive electrode sheet was characterized.
[0051] Figure 1 This is a scanning electron microscope (SEM) cross-sectional view of the nickel cobalt manganese oxide half-cell prepared in Example 1. As shown in the figure, the pole piece directly in contact with pre-lithiation expands by one time and shows uneven expansion, but the pole piece with the pre-lithiation membrane expands uniformly and the volume change is small. The uniform volume expansion indicates that the lithium ions have successfully entered the active material and are evenly distributed, indicating that the pre-lithiation membrane improves the uniformity of the electrode pre-lithiation and does not damage the electrode. The pole piece in the control group that was directly in contact with the pre-lithiation has a dramatic volume expansion, indicating that the structure of the active material of the electrode is damaged due to the excessive rate of lithium ion embedding. This is because during the pre-lithiation reaction, lithium titanate (Li4Ti5O 12 ) is pre-lithiated with lithium metal to form a lithium-conducting material (Li7Ti5O 12 ), whose potential is between that of lithium metal and NCM positive electrode, so it can slowly charge the potential difference brought by direct contact with lithium metal, thereby regulating the lithiation rate and improving the uniformity of electrode lithiation.
[0052] Figure 2 It is a top view, and it can be seen that the positive electrode active material particles in direct contact with lithium metal are broken, which reflects that when in direct contact, the high reactivity of lithium metal will cause local violent reactions (contact interface, large carrier aggregation and combination), and a large amount of heat and gas will be generated, causing the active material at the interface to break, resulting in uneven electrode reactions. However, the electrode using the pre-lithiation membrane maintains the original active material particle structure, indicating that the pre-lithiation membrane regulates the reaction kinetics of contact pre-lithiation, reduces the corrosion of lithium metal on the electrode interface, and improves the stability of the electrode and the uniformity of the reaction.
[0053] Figure 3 The XRD results of the pre-lithiated NCM positive electrode sheet show that the electrode pre-lithiated with the pre-lithiated membrane maintains its original structure, but the characteristic peak of the electrode directly in contact with the pre-lithiated electrode disappears, indicating that its structure is damaged. This result proves that the pre-lithiated membrane achieves lossless pre-lithiation of the positive electrode sheet.
[0054] Based on the above conclusions, the pre-lithiated nickel cobalt manganese oxide positive electrode sheet was further assembled with metallic lithium into a half-cell, and the electrochemical performance of the half-cell was tested. Figure 4 This is the first charge and discharge curve of the nickel cobalt manganese oxide half-cell prepared in Example 1 constructed according to the present invention. Under room temperature conditions, the battery is charged at a constant current of 20mA / g, and the cut-off voltage is 4.3V. As can be seen from the figure, the charging capacity of the nickel cobalt manganese oxide positive electrode without pre-lithiation reaction is 203mAh / g, and the discharge capacity is 180mAh / g. The charging capacity of the pre-lithiation membrane after 1min of pre-lithiation reaction is 208mAh / g, and the discharge capacity is 180mAh / g. The charging capacity of the pre-lithiation membrane after 2min of contact with the pre-lithiation reaction is 220mAh / g, and the discharge capacity is 180mAh / g. This shows that the use of a pre-lithiation membrane in contact with pre-lithiation will not destroy the electrochemical properties of the electrode.
[0055] Example 2
[0056] Take 0.8g silicon powder, 0.1g conductive agent (conductive carbon black) and 0.1g binder (polyacrylic acid), mix the weighed materials evenly, slurry, coat, bake at 80℃ and vacuum conditions for 24h, and punch into electrodes with a diameter of 10mm. Different pre-lithiation membranes are introduced, including stainless steel (SS), copper mesh (Cu mesh), porous copper (Porous Cu), carbon cloth (CC) + lithium belt, and the thickness of the porous membrane is 20μm. Under an inert atmosphere, the silicon negative electrode plate and the pre-lithiation membrane are contacted and pre-lithiated in the electrolyte (0.5MLiDFOB inFEC / DEC) infiltration, where the reaction is carried out at 50℃ for different times, and the pre-lithiated silicon negative electrode can be obtained after drying. The pre-lithiated silicon negative electrode plate is assembled into a half-cell with metallic lithium, and the electrochemical performance of the half-cell is tested.
[0057] Figure 5 These are optical microscope photos of different porous membranes. It can be seen that the porosity of different porous membranes is different, which will lead to different reaction rates. Therefore, selecting pre-lithiation membranes with different porous membranes can regulate the pre-lithiation rate.
[0058] Figure 6This is a SEM cross-sectional view of a silicon negative electrode prepared by using a porous copper + lithium strip pre-lithiation membrane in Example 2 constructed according to the present invention. It can be seen that the silicon electrode pre-lithiated by using the pre-lithiation membrane expands uniformly, while the silicon electrode directly contacting the pre-lithiation exhibits uneven expansion. This result shows that direct contact with lithium metal for pre-lithiation will produce uneven pre-lithiation, which has a side effect on the electrochemical performance of the electrode.
[0059] Figure 7 This is the first charge curve of the silicon half-cell prepared in Example 2 constructed according to the present invention. Under room temperature conditions, the battery is charged at a constant current of 100 mA / g, and the cut-off voltage is 1 V. It can be seen from the figure that the pre-lithiation membranes using different porous membranes can pre-lithiate the negative electrode.
[0060] Example 3
[0061] Take 0.8g of graphite powder, 0.1g of conductive agent (conductive carbon black) and 0.1g of binder (polyacrylic acid), mix the weighed materials evenly, slurry, apply, bake at 80℃ and vacuum conditions for 24h, and punch into electrodes with a diameter of 10mm. Prepare a pre-lithiation membrane with lithium strip and microporous copper membrane (pore size 100nm, thickness 12μm), pre-lithiate the graphite negative electrode plate and pre-lithiation membrane in an inert atmosphere under electrolyte infiltration, react at 0℃ for different times, and dry to obtain a pre-lithiated graphite negative electrode. Assemble the pre-lithiated graphite negative electrode plate and metal lithium into a half-cell, and test the electrochemical performance of the half-cell.
[0062] Figure 8 This is a pre-lithiation time-pre-lithiation capacity curve of the graphite negative electrode half-cell prepared in Example 3 constructed according to the present invention. Under room temperature, the battery is charged at a constant current of 30 mA / g, and the cut-off voltage is 1 V. As can be seen from the figure, the pre-lithiation capacity and time show a linear relationship, and the reaction is uniform, so the pre-lithiation reaction can be precisely controlled.
[0063] Example 4
[0064] Antimony nanopowder and polyamide solution were mixed evenly in a mass ratio of 1:1, and cast into a film to prepare a self-supporting organic-inorganic composite membrane with a pore size of 100nm and a thickness of 50μm. The lithium strip and the composite membrane were assembled together to form a pre-lithiation membrane. In a dry atmosphere, the sulfur cathode electrode and the pre-lithiation membrane were closely contacted under the infiltration of the electrolyte (0.2M LiDFOB in EC:EMC:DMC=1:1:1, volume ratio), and reacted at 0℃ for 2h. After drying, the pre-lithiation sulfur cathode electrode was obtained.
[0065] As can be seen from the above embodiments, the present invention provides a method for pre-lithiation of a lithium-ion battery electrode plate. The present invention uses a pre-lithiation membrane to perform contact pre-lithiation on the lithium-ion battery electrode, and stacks the lithium-ion battery electrode plate and the pre-lithiation membrane by a roll-to-roll method. After adding electrolyte and pressing, the potential difference between the pre-lithiation membrane and the electrode is used to perform a spontaneous self-discharge reaction to achieve a pre-lithiation effect, thereby obtaining a pre-lithiation electrode plate. The pre-lithiation membrane of the present invention can improve the uniformity of electrode pre-lithiation, thereby effectively improving the energy density and cycle life of lithium-ion batteries.
[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for pre-lithiation of a lithium-ion battery electrode sheet, characterized in that: The following steps are involved: The lithium-ion battery electrode sheet and the pre-lithiation membrane are stacked in a roll-to-roll manner under the infiltration of electrolyte, and pre-lithiation is performed after pressing, and a spontaneous self-discharge reaction is performed using the potential difference between the pre-lithiation membrane and the lithium-ion battery electrode sheet; The pre-lithiation membrane is composed of a porous membrane and a lithium belt; The lithium ion battery electrode plate is in direct contact with one side of the porous membrane.
2. The method for pre-lithiation of a lithium-ion battery electrode sheet according to claim 1, characterized in that: The porous membrane comprises one of a porous copper foil, a porous nickel foil, a porous titanium foil, a porous stainless steel mesh, a porous copper-zinc-aluminum alloy membrane, a porous carbon membrane and a porous inorganic-organic composite membrane.
3. The method for pre-lithiation of a lithium-ion battery electrode sheet according to claim 2, characterized in that: The porous inorganic-organic composite membrane comprises an inorganic component and an organic component, wherein the inorganic component comprises one or more of silver, tin, aluminum, magnesium, indium, lead, gold, platinum, silicon, germanium, bismuth, antimony, lithium titanate and aluminum oxide; and the organic component comprises one or more of cellulose, polyamide, polytetrafluoroethylene, polyester, polypropylene, polyethylene, polyethylene oxide, polyvinyl chloride, polysulfone, polyvinylidene fluoride, polyacrylonitrile and polyether sulfone.
4. The method for pre-lithiation of a lithium-ion battery electrode sheet according to any one of claims 1 to 3, characterized in that: The pore diameter of the porous membrane is 0.1 to 200 μm, and the thickness of the porous membrane is 10 μm to 5 mm.
5. The method for pre-lithiation of a lithium-ion battery electrode sheet according to claim 4, characterized in that: The lithium-ion battery electrode plate is a negative electrode plate or a positive electrode plate.
6. The method for pre-lithiation of a lithium-ion battery electrode sheet according to claim 1, 3 or 5, characterized in that: The temperature of the self-discharge reaction is 0-50°C.
7. The method for pre-lithiation of a lithium-ion battery electrode sheet according to claim 6, characterized in that: The negative electrode plate includes one of a silicon-based negative electrode plate, a graphite negative electrode plate, a silicon-carbon negative electrode plate and a silicon-based negative electrode plate; the positive electrode plate includes one of a lithium cobalt oxide positive electrode plate, a nickel-cobalt-manganese-based ternary positive electrode plate and a sulfur positive electrode plate.
Citation Information
Patent Citations
Lithium-ion battery pole piece pre-lithiating device
CN110335992A
Pre-lithiation method of anode for lithium secondary battery, and lithium metal laminate to be used therein
CN110710031A
Continuous, controllable and effective pre-lithiation system and lithium supplementing method
CN111162246A
Preparation method and use method of intermediate buffer film of silicon-based negative electrode of pre-lithiated lithium ion battery
CN112750984A
Method for forming lithium metal and inorganic material composite thin film and method for pre-lithiation of negative electrode for lithium secondary battery by using same
US20200136128A1
